You are on page 1of 2

Chapter 2

Nonlinear Equations

A fundamental principle in computer science is iteration. Iterative techniques are


used to find roots of equations, solutions of linear and nonlinear systems of equations,
and solutions of differential equations.

2.1 Newton–Raphson Method


We consider the nonlinear equation

x = g(x).

Let f (x) = x − g(x) = 0.


If f (x), f 0 (x), and f 00 (x) are continuous near a root x, then this extra information
regarding the nature of f (x) can be used to develop algorithms that will produce
sequences {xk } that converge faster to x than either the bisection or false position
methods. The Newton–Raphson method is one of the most useful and best known
algorithms that rely on the continuity of f 0 (x) and f 00 (x).
Assume that f ∈ C 2 [a, b] and there exists a number x ∈ [a, b] where f (x) = 0. If
0
f (x) 6= 0, then there exists a δ > 0 such that the sequence {xk }∞ k=0 defined by the
iteration
f (xk−1 )
xk = g(xk−1 ) = xk−1 − 0 , for k = 1, 2, . . .
f (xk−1 )
will converges to x for any initial approximation x0 ∈ [x − δ, x + δ].

Example 2.1

Find a root of the equations 3x3 − 10x + 3 = 0 with x0 = 0.1 by Newton–Raphson


method with a tolerance of 0.001.
Solution:
x0 = 1

f (x) = 3x3 − 10x + 3,


f 0 (x) = 9x2 − 10

10
11

We have the Newton–Raphson method


f (xk−1 )
xk = xk−1 − , for k = 1, 2, . . .
f 0 (xk−1 )
Therefore,
3x3k−1 − 10xk−1 + 3
xk = xk−1 − for k = 1, 2, . . .
9x2k−1 − 10

3x30 − 10x0 + 3
x1 = x0 −
9x20 − 10
= 0.3

3x31 − 10x1 + 3
x2 = x1 −
9x21 − 10
= 0.3088

3x32 − 10x2 + 3
x3 = x2 −
9x22 − 10
= 0.3088

2.2 Secant Method


The secant method is given by the two–point iteration formula
f (xk ) (xk − xk−1 )
xk+1 = g(xk , xk−1 ) = xk − for k = 1, 2, . . . .
f (xk ) − f (xk−1 )
Example 2.2
Use the secant method to find the root of the polynomial function f (x) = x3 −3x+2
with x0 = −2.6 and x1 = −2.4.
Solution: The iteration formula of secant method is
f (xk ) (xk − xk−1 )
xk+1 = g(xk , xk−1 ) = xk − for k = 1, 2, . . . .
f (xk ) − f (xk−1 )

(x3k − 3xk + 2)(xk − xk−1 )


xk+1 = xk −
x3k − x3k−1 − 3xk + 3xk−1

k = 1, x2 = −2.1066
k = 2, x3 = −2.0226
k = 3, x4 = −2.0015
k = 4, x5 = −2.0000

You might also like